Rethinking 'classical yoga' and buddhism: meditation, metaphors and materiality - O'Brien-Kop, Karen (Bloomsbury advances in religious studies, 2022)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- Tables -- Preface -- Acknowledgements -- Abbreviations -- Note on translation and transliteration -- Introduction 'Classical yoga' and Buddhism: Debates, dialogue and intertextuality -- 1 Mokṣa, metaphors and materiality: Concepts and contexts of 'liberation' -- 2 Seeds of bondage and freedom: Eliminating the afflictions (klesas) in the Patañjalayogasastra and the Abhid -- 3 The 'other' yoga sastra: The Yogacarabhumisastra -- 4 Patañjala yoga and yogacara: The cultivation of the counterstate -- 5 Who put the classical in 'classical yoga'? The inadequacy of an analytical category -- Conclusion: Rethinking 'classical yoga' - a categorical paradigm shift? -- Appendix 1 A note on the title Patañjalayogasastra -- Appendix 2 Classical Indian metaphor theory -- Appendix 3 Structure of the Yogacarabhumisastra -- Notes -- Bibliography -- Index.